Comparative Marketing: The First Twenty five Years - Boddewyn, Jean J. (Journal of International Business Studies, 1981)
This article reviews the field of Comparative Marketing in terms of scope, types, and depth of studies; methodological issues, conceptual and managerial payoffs, and teaching approaches. After its first quarter of a century as an international business topic, Comparative Marketing is still relatively green.